Tooth-supported overdenture retained with metal medium copings: A case report - I Gede Made Hadi Nugraha Arisukra; Titik Ismiyati (Indonesian Journal of Prosthodontic, 2024)
Overdenture is removable denture used to replace missing teeth and cover or rest on one or more remaining natural teeth in the mouth. The concept of overdenture is a positive means for delaying the process of complete edentulism and helps in reducing bone resorption. Selection of teeth to be retained by looking at periodontal tissue and history of dental caries. Tooth-supported overdenture using coping can be made with short coping, medium coping, or long coping. Metal copings can be used on teeth that have decreased alveolar bone support but are still strong, also covering dentin tubules. On this report, A 62-year-old man patient reported having the chief complaint of difficulty in chewing food and speaking due to missing teeth in the upper and lower arch. This case report describes prosthodontic rehabilitation of a mandibular partially edentulous arch with tooth-supported overdenture using metal medium copings which aim to provide sensory response with further stability and retention to the denture. The patient was satisfied with the treatment outcome. For elderly edentulous patient with few remaining teeth, a tooth-supported overdenture is one of the best and most practical, feasible, and comfortable treatment alternatives.